Comparative leaf anatomy of lulo (Solanum quitoense Lam.) materials with and without thorns (2008)
A study was carried out to describe the lulo (Solanum quitoense Lam.) leaf anatomy of materials with thorns (CE, accession ‘NM’) and thorn less (SE, accession ’SV80’) under full sun exposure, in the upper, middle and lower plant strata, during the vegetative and productive phases. No significant morphological differences between the leaf structures of both genotypes were found during the ontogenic studied periods. Both presented an adaxial and abaxial monostratified layer leaf epidermis of equidimensional or rectangular cells with the presence of stelate, non glandular trichoma, being more abundant at the lower leaf epidermis; and idioblasts with calcium oxalate crystals. Chloroplasts were evident throughout the mesophyll, with greater frequency in the upper and middle strata. A compact palisade parenchyma was exhibited in the upper an middle strata, and presence of intercellular spaces in the lower strata. Differences in width and length of the palisade parenchyma cell size were evident, between plant strata and ecotypes. Similar to C3 plants and in the range of other Solanaceae species, leaf stomas were mainly located at the lower leaf epidermis, with an insignificant amount of them at the upper epidermis.